The Pre-Modern Manuscript Trade and Its Consequences, Ca. 1890-1945. - Cleaver, Laura; Magnusson, Danielle; Morcos, Hannah; Rais, Angéline. (Amsterdam : Arc Humanities Press, 2024)
This book is Open Access and available from OAPEN. This collection brings together current research into the development of the market for pre-modern manuscripts between 1890 and 1945, and its impact.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books